Gastrointestinal mucosal abnormalities using videocapsule endoscopy in systemic sclerosis. Issue 2 (2nd June 2014) - Marie, I.; Antonietti, M.; Houivet, E.; Hachulla, E.; Maunoury, V.; Bienvenu, B.; Viennot, S.; Smail, A.; Duhaut, P.; Dupas, J ‐L.; Dominique, S.; Hatron, P.‐Y.; et al.
Summary Background To date, there are no large studies on videocapsule endoscopy in systemic sclerosis (SSc). Consequently, the prevalence and features of gastrointestinal mucosal abnormalities in SSc have not been determined. Aims To determine both prevalence and characteristics of gastrointestinal mucosal abnormalities in unselected patients with SSc, using videocapsule endoscopy. To predict which SSc patients are at risk of developing potentially bleeding gastrointestinal vascular mucosal abnormalities. Methods Videocapsule endoscopy was performed on 50 patients with SSc. Results Prevalence of gastrointestinal mucosal abnormalities was 52%. Potentially bleeding vascular mucosal lesions were predominant, including: watermelon stomach (34.6%), gastric and/or small intestinal telangiectasia (26.9%) and gastric and/or small intestinal angiodysplasia (38.5%). SSc patients with gastrointestinal vascular mucosal lesions more often exhibited: limited cutaneous SSc (P = 0.06), digital ulcers (P = 0.05), higher score of nailfold videocapillaroscopy (P = 0.0009), anaemia (P = 0.02), lower levels of ferritin (P < 0.0001) and anti‐centromere antibody. Conclusions Our study identifies a high frequency of gastrointestinal mucosal abnormalities in SSc, with a marked predominance of vascular mucosal damage. Furthermore, our study shows a strong correlation between gastrointestinal vascular mucosal lesions and presence of severe extra‐digestive vasculopathy (digital ulcers and higher nailfold videocapillaroscopy scores). This latter supports the theory that SSc‐related diffuse vasculopathy is responsible for both cutaneous and digestive vascular lesions. Therefore, we suggest that nailfold videocapillaroscopy may be a helpful test for managing SSc patients. In fact, nailfold videocapillaroscopy score should be calculated routinely, as it may result in identification of SSc patients at higher risk of developing potentially bleeding gastrointestinal vascular mucosal lesions.